Pengaruh Tingkat Pendidikan, Masa Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Bappeda Litbang Kabupaten Ponorogo - Sayekti, Nur - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
ABSTRAKHasil penelitian ini menunjukkan bahwa:  1) Tingkat pendidikan berpengaruh positif dan signfikan terhadap kinerja pegawai Bappeda Litbang Kabupaten Ponorogo. Hal ini dibuktikan nilai hasil  thitung sebesar 4,106 dengan nilai probabilitas (0,000) < 0,05 maka Ho ditolak atau Ha diterima berarti terdapat pengaruh yang positif dan signifikan tingkat pendidikan terhadap kinerja  pegawai Bappeda Litbang Kabupaten  Ponorogo. 2) Masa kerja tidak berpengaruh positif  dan signfikan terhadap kinerja Pegawai Bappeda Litbang Kabupaten Ponorogo. Hal ini dibuktikan nilai hasil  thitung sebesar  1.785 dengan nilai probabilitas (0,082) > 0,05 maka Ho diterima atau Ha ditolak berarti terdapat tidak  berpengaruh  masa kerja terhadap kinerja  pegawai Bappeda Litbang Kabupaten  Ponorogo. 3) Motivasi kerja berpengaruh positif dan signfikan terhadap kinerja kinerja Pegawai Bappeda Litbang Kabupaten Ponorogo.  Hal ini dibuktikan nilai hasil  thitung sebesar 6.405  dengan nilai probabilitas (0,000) < 0,05 maka Ho ditolak atau Ha diterima berarti terdapat pengaruh yang positif dan signifikan motivasi kerja terhadap kinerja  pegawai Bappeda Litbang Kabupaten  Ponorogo. Kata kunci: Tingkat pendidikan, masa kerja, motivasi kerja dan kinerja    ABSTRACT The population of this research is all BAPPEDA Litbang Ponorogo employees, amounting to 43 people. Data collection techniques using a questionnaire that has passed the test of validity and reliability. The regression requirements test uses the classic assumption test. Data analysis techniques using multiple linear regression analysis and hypothesis testing is done through t test.The results of this study indicate that: 1) The level of education has a positive and significant effect on the performance of the Bappeda Research and Development Agency in Ponorogo Regency. This is evidenced by the value of the tcount of 4.106 with a probability value (0,000) <0.05 then Ho is rejected or Ha is accepted, meaning there is a positive and significant influence on the level of education on the performance of the Bappeda R & D Ponorogo District employees. 2) The length of service does not have a positive and significant effect on the performance of the Bappeda Research and Development Agency in Ponorogo Regency. This is proven by the value of the t-test result of 1,785 with a probability value (0.082)> 0.05 then Ho is accepted or Ha is rejected, meaning that there is no effect on the working period of the performance of the Bappeda Litbang Ponorogo employee. 3) Work motivation has a positive and significant effect on the performance of the Bappeda Research and Development Agency in Ponorogo Regency. This is evidenced by the value of the tcount of 6,405 with a probability value (0,000) <0.05 then Ho is rejected or Ha is accepted, meaning there is a positive and significant influence of work motivation on the performance of the Bappeda R & D employee in Ponorogo Regency. Keywords: Level of education, years of service, work motivation and performance